Merawat Kekompakan: Mengurai Dinamika Komunikasi dalam Hubungan Keluarga Jawa antara Suami dan Istri - Suparno, Basuki Agus; Indah, Sika Nur; Hasanah, Khuswatun (Jurnal Pekommas, 2024)
The dynamics of couples' relationships significantly impact a family's unity and harmony. This hinges on how spouses interact and communicate, influenced by patriarchal or matrilineal views they uphold. Communication dynamics in these relationships direct family goals. This study delves into how Javanese couples nurture their bonds. Employing qualitative methods, it includes in-depth interviews and group discussions with seven couples, selected based on education, socio-economic status, marriage duration, careers, religious values, and motives. Findings show Javanese couples favor dialogue over conflict, opting for a collaborative and compromising approach. They uphold mutual trust and flexibility in financial matters ("sing longgar endi"). Family discussions during tension aim to preserve collective values. Domestic work communication highlights flexibility in task distribution. The research underscores Javanese couples' connection to unique ethics, social norms, philosophies, gender perspectives, structures, language, traditions, myths, and religion.